Paracapnia humboldta (Plecoptera: Capniidae), a new winter stonefly from northern California, U.S.A. - Baumann, Richard W. (Illiesia, 2007)
Paracapnia humboldta, n.sp., is described from specimens collected at Mason Gulch in the Coast Range of northern California. The new species is compared to the three named species that occur in the Pacific coastal states.
Keywords: entomologija; Plecoptera; žuželke; vrbnice; California; Kalifornija; United States of America; ZDA